Simultaneous introduction of a novel high fat diet and wheel running induces anorexia - Scarpace, E.T.; Matheny, M.; Strehler, K.Y.E.; Shapiro, A.; Cheng, K.Y.; Tümer, N.; Scarpace, P.J. (Physiology & behavior, 2012)
Voluntary wheel running (WR) is a form of physical activity in rodents that influences ingestive behavior. The present report describes an anorexic behavior triggered by the simultaneous introduction of a novel diet and WR. This study examined the sequential, compared with the simultaneous, introduction of a novel high-fat (HF) diet and voluntary WR in rats of three different ages and revealed a surprising finding; the simultaneous introduction of HF food and voluntary WR induced a behavior in which the animals chose not to eat although food was available at all times. This phenomenon was apparently not due to an aversion to the novel HF diet because introduction of the running wheels plus the HF diet, while continuing the availability of the normal chow diet did not prevent the anorexia. Moreover, the anorexia was prevented with prior exposure to the HF diet. In addition, the anorexia was not related to extent of WR but dependent on the act of WR. The introduction a HF diet and locked running wheels did not induce the anorexia. This voluntary anorexia was accompanied by substantial weight loss, and the anorexia was rapidly reversed by removal of the running wheels. Moreover, the HF/WR-induced anorexia is preserved across the age span despite the intrinsic decrease in WR activity and increased consumption of HF food with advancing age. The described phenomenon provides a new model to investigate anorexia behavior in rodents. ► Concurrent introduction of running wheels and a high-fat diet induced anorexia. ► The anorexia did not occur if the rats were pre-exposed to the high-fat diet. ► The anorexia was not due to an aversion to the high-fat diet. ► Aged and young rats that run to different extents displayed the same anorexia. ► This may represent a new model to investigate anorectic behavior in rodents.